Broad-scale informed consent: A survey of the CTSA landscape. Issue 5 (23rd October 2019) - Chandler, Redonna; Brady, Kathleen T.; Jerome, Rebecca N.; Eder, Milton; Rothwell, Erin; Brownley, Kimberly A.; Harris, Paul A.
Abstract: Introduction: Research opportunities associated with the proliferation of the electronic health record (EHR), big data initiatives, and innovative approaches to trial design can present challenges for obtaining and documenting informed consent. Broad-scale informed consent (a term used herein to describe institutional models, rather than the Common Rule's strict regulatory definition for "broad consent") may facilitate the use of existing data and samples and speed the pace of research by minimizing barriers to consent. We explored the use of broad-scale informed consent within the Clinical Translational Science Award (CTSA) Program Network. Methods: We surveyed CTSA Hubs concerning policies, practices, experiences, and needs within three domains of broad-scale informed consent: (1) participant recontact; (2) biospecimens; and (3) clinical data sharing. Results: Of 61 CTSA Hubs surveyed, 37 (61%) indicated ongoing work related to at least 1 domain of broad-scale informed consent; 18 Hubs (30%) reported work in all 3 domains. The EHR predominated as the implementation system across all three domains. Research and IT leadership and the Institutional Review Board were most commonly endorsed as institutional drivers, while systems/technical issues and impact on clinical workflow were the most commonly reported barriers. Conclusions: While survey results indicate considerable variability in the implementation of broad-scale informed consent across the CTSA consortium, it is clear that all CTSA Hubs are actively considering policy and process related to these concepts. Next steps cluster within three areas: training and workforce development, streamlined policies and templates, and implementation strategies that facilitate integration into clinical workflow.